2011
DOI: 10.1073/pnas.1019419108
|View full text |Cite
|
Sign up to set email alerts
|

Water molecule reorganization in cytochrome c oxidase revealed by FTIR spectroscopy

Abstract: Although internal electron transfer and oxygen reduction chemistry in cytochrome c oxidase are fairly well understood, the associated groups and pathways that couple these processes to gated proton translocation across the membrane remain unclear. Several possible pathways have been identified from crystallographic structural models; these involve hydrophilic residues in combination with structured waters that might reorganize to form transient proton transfer pathways during the catalytic cycle. To date, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…The recent FTIR experiment also confirmed that the hydrogen bond network rearrangement occurs in response to the oxidation state change. 34 Also, Wikström, et al reported that the hydrogen bond network of the water cluster in the non-polar cavity is changed by change of oxidation states of heme a and the BNC, although their empirical MD simulations included no excess proton. 13 …”
Section: Resultsmentioning
confidence: 99%
“…The recent FTIR experiment also confirmed that the hydrogen bond network rearrangement occurs in response to the oxidation state change. 34 Also, Wikström, et al reported that the hydrogen bond network of the water cluster in the non-polar cavity is changed by change of oxidation states of heme a and the BNC, although their empirical MD simulations included no excess proton. 13 …”
Section: Resultsmentioning
confidence: 99%
“…31 Later, dangling and weakly H-bonded water molecules have been also detected at room temperature. [32][33][34] Changes in the D-O-D bending of water molecules have been detected, as well. 35 It was shown that the exchange of the protein solvent from H 2 16 O to H 2 18 O is enough to detect dangling waters in the dark state of BR, without the need to induce a photoreaction.…”
mentioning
confidence: 88%
“…1A, and see below). Even though there is little direct experimental support available for such a water-gated mechanism, a recent FTIR study indeed suggests changes in water organization upon changes in the redox state of the enzyme (11). Many of the elementary steps that were postulated in the water-gated mechanism have gained support from experiments in the recent past (12,13).…”
mentioning
confidence: 99%